Comparison of Single and Group Jet Grouting Columns Capacity Based on Field Load Test and Theoretical Methods - Al-Kinani, Ali M.; Ahmed, Mahmood D. (Civil Engineering Journal, 2019)
The evaluation of axial capacity of jet grouted soil cement columns in soft soil is a complicated issue because it depends according to the number of factors such as, soil type, influence mixture between soil and grouting materials, nozzle jet energy, jet grouting and water flow rate, rotation and lifting speed. These parameters related to the type of jet grouting methods (single, double and triple system). Most methods of design the bearing capacity of the jet-grouting column based on experience. Therefore, some designer calculates the bearing capacity of the jet grouting column based on jet grout section capacity. In this paper, different theoretical methods have been used to estimate of the jet grouting soil-cement capacity, such as Poulos and Davis, 1980 methods and then their comparison with the pile load test calculations based on the quick pile load test as presented in ASTM-D1143-07. Therefore, the study describes a prototype test single and group jet grout soil-cement models of arrangement (1*1, 1*2 and 2*2) for total length to diameter ratios (L/D) is 13.33 and clear spacing three times of diameter has been constructed in soft clayey soils in the right bank of the Euphrates River, at Al- Nasiriyah city. As a result, the theoretical method for estimation the bearing capacity gives unfaithful values for the single and group jet grout column compared to the load- settlement calculations obtained from field pile load test data. On the other hand, the Hansen’s 90% and Butler and Hoy’s given closer results to each other and may be considered faithful interpretation methods to compute the bearing capacity of single and group jet grouting columns.